2020
DOI: 10.37506/ijop.v8i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computer Usage on Visual Reaction Time in Information Technology Professionals of Bangalore City

Abstract: Background: Reaction time is the elapsed time between presentation of a sensory stimulus and the subsequent behavioural response. Time taken to respond to visual stimulus gives visual reaction time. In the modern world, the usage of computers for occupational purpose is increasing with increased duration of usage, especially in IT profession. Few studies have been done on reaction time in mobile phone users and video game players, but no study is done in occupational computer users.Objective: To compare visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Neck pain is a common complaint, and its occurrence is 64 % more frequent than other upper quarter problems in computer users [5]. Sreenivasan et al reported an incidence rate of 44 % of neck pain in the Indian population of computer users [7]. Computer work poses numerous physical risks.…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is a common complaint, and its occurrence is 64 % more frequent than other upper quarter problems in computer users [5]. Sreenivasan et al reported an incidence rate of 44 % of neck pain in the Indian population of computer users [7]. Computer work poses numerous physical risks.…”
Section: Introductionmentioning
confidence: 99%